High and low temperature resistant butterfly insulator and preparation method thereof

CN122940439APending Publication Date: 2026-10-20南昌永基电气技术有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611395849.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]但是,瓷绝缘子由于瓷体、釉层与金属附件之间的热膨胀系数存在差异,在-40℃至80℃乃至更大温差的高低温循环服役环境下,温度交替变化会使各界面产生交变热应力,长期作用下釉面易萌生微裂纹并逐步扩展,加速瓷体老化、降低绝缘性能、缩短使用寿命,且温差为100℃的热震试验条件下存在开裂风险;与此同时,瓷绝缘子表面憎水性差,在潮湿污秽环境下易发生污闪,导致现有的瓷绝缘子在耐高低温性能、机械强度与长期服役可靠性等方面难以全面满足严苛服役环境的要求,有待改进

Benefits of technology

1、通过作为负热膨胀材料的Sc2W3O12壳核粉体与瓷体中的正热膨胀组分形成热膨胀补偿效应,有效降低了瓷体的热膨胀系数,显著提升绝缘子在剧烈温度交变环境下的抗热震能力。同时,Al2O3壳层与瓷体各组分之间具有良好的相容性,有效避免Sc2W3O12核层与瓷体间的热应力集中现象,进而起到增强温度循环稳定性的作用。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This application discloses a high and low temperature resistant butterfly insulator and its preparation method, relating to the field of ceramic insulator technology. The insulator includes a ceramic body comprising 25-35 parts by weight of kaolin, 12-20 parts by weight of feldspar, 8-14 parts by weight of quartz, and 8-15 parts by weight of Sc2W3O. 12 The composition comprises: core-shell powder, 3-8 parts of high-entropy oxide, 2-5 parts of B2O3, 0.5-2 parts of P2O5, 0.3-1.5 parts of Li2O, and 3-6 parts of nano-Al2O3; wherein: the Sc2W3O 12 Core-shell powder is composed of Sc2W3O 12 The core layer is composed of an Al2O3 shell; the high-entropy oxide is (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 This application significantly improves high and low temperature resistance, mechanical strength, and long-term service reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of ceramic insulator technology, and in particular to a high and low temperature resistant butterfly insulator and its preparation method. Background Technology

[0002] Butterfly insulators, also known as butterfly-shaped insulators, are widely used insulation devices in overhead power transmission and distribution lines. They serve the dual functions of electrical isolation and mechanical fixation, and are typically installed on tension poles, angle poles, and terminal poles to support and fix conductors while isolating live conductors from the electrical gaps between the conductors and the tower. Their insulation performance and mechanical reliability directly affect the safe and stable operation of the power distribution line. With the construction of new power systems and the continuous expansion of harsh service environments such as high altitudes, cold regions, and large temperature differences, power distribution lines are placing increasingly higher demands on the insulation performance, mechanical strength, and resistance to high and low temperatures of butterfly insulators.

[0003] Existing butterfly insulators are mainly classified into two categories based on their materials: porcelain insulators and composite insulators. Traditional porcelain butterfly insulators use electrical ceramics as the base material. The formula typically consists of inorganic non-metallic mineral raw materials such as kaolin, feldspar, and quartz, with kaolin accounting for approximately 45%, feldspar approximately 30%, and quartz approximately 20%. The remainder consists of reinforcing and modifying additives such as alumina and zirconium oxide. After raw material processing, ball milling, filtration to remove iron, pressing, molding, air-drying, and glazing, the insulators are sintered in a high-temperature kiln at 1200℃–1400℃ to form porcelain. Finally, cement is used to attach iron caps and steel feet to create the finished product. Some high-performance products utilize a high-alumina porcelain formula reinforced with alumina and zirconium oxide to achieve higher mechanical strength.

[0004] However, due to the differences in the coefficients of thermal expansion between the porcelain body, glaze layer, and metal fittings, porcelain insulators are subject to alternating thermal stress at various interfaces under high and low temperature cyclic service environments with temperature differences ranging from -40℃ to 80℃ or even greater. Over long-term exposure, microcracks are prone to develop on the glaze surface and gradually expand, accelerating the aging of the porcelain body, reducing insulation performance, and shortening service life. Furthermore, there is a risk of cracking under thermal shock testing conditions with a temperature difference of 100℃. At the same time, porcelain insulators have poor hydrophobicity, making them prone to flashover in humid and polluted environments. Consequently, existing porcelain insulators cannot fully meet the requirements of harsh service environments in terms of high and low temperature resistance, mechanical strength, and long-term service reliability, and therefore require improvement. Summary of the Invention

[0005] In view of this, the first objective of this application is to provide a high and low temperature resistant disc insulator to significantly improve its high and low temperature resistance, mechanical strength, and long-term service reliability. The specific solution is as follows: A high- and low-temperature resistant butterfly insulator includes a porcelain body, wherein the porcelain body comprises 25-35 parts by weight of kaolin, 12-20 parts by weight of feldspar, 8-14 parts by weight of quartz, and 8-15 parts by weight of Sc2W3O. 12 The composition includes core-shell powder, 3-8 parts of high-entropy oxides, 2-5 parts of B2O3, 0.5-2 parts of P2O5, 0.3-1.5 parts of Li2O, and 3-6 parts of nano-Al2O3; wherein: The Sc2W3O 12 Core-shell powder is composed of Sc2W3O 12 The core is composed of an Al2O3 shell. The high-entropy oxide is (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O.

[0006] Preferably: the Sc2W3O 12 The core-shell powder was prepared by the sol-gel method, and the preparation method involved preparing Sc2W3O 12 Micronized powder is dispersed in an aluminum alkoxide solution, and undergoes hydrolysis and condensation to form an Al(OH)3 shell. Pre-calcination at a controlled temperature of 590-610℃ yields an α-Al₂O₃ shell with a thickness of 0.2-0.5 μm and a Sc₂W₃O₃ shell with a D50 of 1-5 μm. 12 Sc2W3O composed of core layers 12 Core-shell powder.

[0007] Preferably, the aluminum alkoxide solution is an isopropanol solution of aluminum isopropoxide, and the aluminum isopropoxide reacts with Sc2W3O. 12 The mass ratio of the micro powder is (0.3-0.8):1; the pH of the hydrolysis and condensation solution is 4-6, the stirring speed is 200-500 r / min, and the hydrolysis time is 4-8h.

[0008] Preferably: the (Mg) 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 The preparation method of O is as follows: Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2 are dissolved in deionized water in an equimolar ratio, and then citric acid is added and evaporated in a water bath to form a gel. After pre-calcination and high-temperature calcination, high-entropy oxide powder with a particle size of 50-200 nm is obtained. The molar ratio of citric acid to metal ions is (1.2-1.8):1; the water bath evaporation temperature is 78-82℃; the pre-calcination temperature is 380-420℃; and the high-temperature calcination temperature is 780-850℃.

[0009] Preferably, the product further includes a glaze layer for coating the outer surface of the porcelain body; the glaze layer comprises 70-80 parts by weight of a base glaze and 5-10 parts by weight of Sc2W3O. 12 Micronized powder, 2-4 parts of nano ZrO2 and 1-3 parts of B2O3; the base glaze is a feldspar-quartz-lime glaze matrix.

[0010] The second objective of this application is to provide a method for preparing a high- and low-temperature resistant butterfly insulator, which is used to prepare the high- and low-temperature resistant butterfly insulator as described above, comprising the following steps: Step 1, Ball Milling: Mix the appropriate weight parts of kaolin, feldspar, quartz, nano-Al2O3, and Sc2W3O 12 Shell-core powder, high-entropy oxide, B2O3, P2O5 and Li2O are mixed, and after adding deionized water and dispersant, the mixture is ball-milled for 12-24 hours to obtain a mixed slurry with a particle size D50 of 2-5μm. Step 2, Iron Removal and Molding: The mixed slurry is sieved to remove iron, and after pressing and vacuum kneading, it is shaped to obtain the butterfly insulator porcelain blank; Step 3, Drying: Place the butterfly insulator porcelain blank in the shade at a temperature of 40-60℃ for 24-48 hours, and then dry it at a temperature of 100-120℃ until the moisture content is less than 0.5% to obtain the dried porcelain blank; Step 4, Biscuit firing: Place the dried porcelain blank at a temperature of 850-950℃ for 1-2 hours, and then cool it to room temperature in the kiln to obtain the biscuit fired porcelain blank. Step 5, Glazing and final firing: Apply glaze to the surface of the bisque porcelain blank, control the glaze thickness to be 0.3-0.6mm, then control the heating rate to 1-5℃ / min to raise the temperature to 1280-1320℃, hold for 2-4 hours and cool with the furnace to room temperature to obtain the finished high and low temperature resistant butterfly insulator.

[0011] Preferably, in step 1, the alumina grinding balls are used for ball milling, and the ball-to-material mass ratio is controlled to be (2-4):1, and the rotation speed is 200-350 r / min; the dispersant is sodium tripolyphosphate or ammonium polyacrylate, and the amount added is controlled to be 0.2-0.8% of the total mass of the ceramic body.

[0012] Preferably, in step 2, the molding process is isostatic pressing or grouting. The molding pressure of the isostatic pressing is 150-250 MPa and the holding time is 30-90 s. The grout specific gravity of the grout in the grouting process is 1.75-1.90 and the grouting time is 15-40 min.

[0013] Preferably, in step 5, the glazing is performed using a glaze slurry, either by dipping or spraying, with the dipping time controlled to be 3-8 seconds or the spraying thickness to be 0.3-0.6 mm; the glaze slurry consists of 70-80 parts by weight of a base glaze and 5-10 parts by weight of Sc2W3O. 12 Micronized powder, 2-4 parts of nano ZrO2 and 1-3 parts of B2O3 are ball-milled for 8-12 hours, and deionized water is added and the specific gravity of the glaze slurry is controlled to be 1.45-1.65.

[0014] Preferably, in step 5, the temperature is first raised from room temperature to 600℃ at a rate of 1-2℃ / min; then raised to 1100℃ at a rate of 2-4℃ / min; and finally raised to 1280-1320℃ at a rate of 1-3℃ / min. The cooling rate during furnace cooling is less than 3℃ / min.

[0015] As can be seen from the above solutions, this application provides a high and low temperature resistant butterfly insulator and its preparation method, which has the following beneficial effects: 1. Using Sc2W3O as a negative thermal expansion material 12 The core powder and the positively expanding components in the ceramic body form a thermal expansion compensation effect, effectively reducing the coefficient of thermal expansion of the ceramic body and significantly improving the thermal shock resistance of the insulator under severe temperature alternation. Simultaneously, the Al2O3 shell exhibits good compatibility with the various components of the ceramic body, effectively avoiding the problems associated with Sc2W3O. 12 The thermal stress concentration phenomenon between the core layer and the ceramic body enhances the stability of temperature cycling.

[0016] 2. Through the high-entropy effect and lattice distortion effect of high-entropy oxides, the densification of the ceramic body during sintering is effectively promoted; and the dispersion strengthening of nano-Al2O3 and Sc2W3O 12 The core-shell structure of the powder works synergistically to enhance the grain boundary bonding strength, thereby significantly improving the flexural strength and mechanical reliability of the ceramic body.

[0017] 3. By adding Sc2W3O to the glaze layer on the outside of the porcelain body 12 Micronized powder and B2O3 effectively regulate the thermal expansion coefficient of the glaze, avoiding problems such as cracking and peeling of the glaze caused by thermal expansion mismatch. In addition, the phase transformation toughening effect of nano ZrO2 improves the crack resistance of the glaze, so as to achieve long-term service reliability under extreme temperature conditions. Detailed Implementation

[0018] The technical solutions described below in conjunction with the embodiments of this application will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0019] The following will provide a detailed description of a high and low temperature resistant butterfly insulator and its preparation method.

[0020] A high- and low-temperature resistant butterfly insulator includes a porcelain body and a glaze layer for covering the outer surface of the porcelain body. The porcelain body comprises 25-35 parts by weight of kaolin, 12-20 parts by weight of feldspar, 8-14 parts by weight of quartz, and 8-15 parts by weight of Sc2W3O. 12 The composition consists of core-shell powder, 3-8 parts of high-entropy oxides, 2-5 parts of B2O3, 0.5-2 parts of P2O5, 0.3-1.5 parts of Li2O, and 3-6 parts of nano-Al2O3.

[0021] Sc2W3O 12 Core-shell powder is composed of Sc2W3O 12 The core is composed of an Al₂O₃ shell. Sc₂W₃O 12 The core-shell powder was prepared by the sol-gel method, and the preparation method involved preparing Sc2W3O 12 Micronized powder is dispersed in an aluminum alkoxide solution, and undergoes hydrolysis and condensation to form an Al(OH)3 shell. Pre-calcination at a controlled temperature of 590-610℃ yields an α-Al₂O₃ shell with a thickness of 0.2-0.5 μm and a Sc₂W₃O₃ shell with a D50 of 1-5 μm. 12 Sc2W3O composed of core layers 12 Core-shell powder. In the embodiments of this application, the aluminum alkoxide solution is an isopropanol solution of aluminum isopropoxide, and aluminum isopropoxide reacts with Sc2W3O. 12 The mass ratio of the micronized powder is (0.3-0.8):1. The pH of the hydrolysis and condensation solution is 4-6, the stirring speed is 200-500 r / min, and the hydrolysis time is 4-8 h.

[0022] It should be noted that the high-entropy oxide is (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O.

[0023] (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2The preparation method of O is as follows: Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2 are dissolved in deionized water in an equimolar ratio. Citric acid with a molar ratio of (1.2-1.8):1 to the metal ions is then added. The mixture is evaporated in a water bath at 78-82℃ to form a gel. After pre-calcination at 380-420℃ and high-temperature calcination at 780-850℃, high-entropy oxide powder with a particle size of 50-200 nm is obtained. The glaze layer includes 70-80 parts by weight of a base glaze and 5-10 parts by weight of Sc2W3O. 12 Micronized powder, 2-4 parts nano ZrO2, and 1-3 parts B2O3. The base glaze is a feldspar-quartz-lime glaze matrix, commercially available.

[0024] A method for preparing a high and low temperature resistant butterfly insulator, used to prepare the high and low temperature resistant butterfly insulator as described above, includes the following steps: Step 1, Ball Milling: Mix the appropriate weight parts of kaolin, feldspar, quartz, nano-Al2O3, and Sc2W3O 12 Core-shell powder, high-entropy oxide, B2O3, P2O5, and Li2O are mixed, and after adding deionized water and a dispersant, the mixture is ball-milled for 12-24 hours to obtain a mixed slurry with a particle size D50 of 2-5 μm. The alumina grinding balls are used for ball milling, with a ball-to-powder mass ratio controlled at (2-4):1, and a rotation speed of 200-350 r / min. The dispersant is sodium tripolyphosphate or ammonium polyacrylate, and its addition amount is controlled at 0.2-0.8% of the total mass of the ceramic body.

[0025] Step 2, Iron Removal and Molding: The mixed slurry is sieved to remove iron, then pressed and vacuum-kneaded before molding to obtain the butterfly insulator porcelain blank. The molding process can be either isostatic pressing or grouting. For isostatic pressing, the molding pressure is 150-250 MPa, and the holding time is 30-90 seconds. For grouting, the slurry specific gravity is 1.75-1.90, and the grouting time is 15-40 minutes.

[0026] Step 3, Drying: Place the butterfly insulator porcelain blank in the shade at a temperature of 40-60℃ for 24-48 hours, and then dry it at a temperature of 100-120℃ until the moisture content is less than 0.5% to obtain the dried porcelain blank.

[0027] Step 4, Biscuit firing: Place the dried porcelain blank at a temperature of 850-950℃ for 1-2 hours, and then cool it to room temperature in the kiln to obtain the biscuit fired porcelain blank.

[0028] Step 5, Glazing and final firing: Apply glaze to the surface of the bisque porcelain blank, control the glaze thickness to be 0.3-0.6mm, then control the heating rate to 1-5℃ / min to raise the temperature to 1280-1320℃, hold for 2-4 hours and cool with the furnace to room temperature to obtain the finished high and low temperature resistant butterfly insulator.

[0029] The glazing process involves using a glaze slurry, applied via dipping or spraying, with the dipping time controlled to 3-8 seconds or the spraying thickness to 0.3-0.6 mm. The glaze slurry consists of 70-80 parts by weight of a base glaze and 5-10 parts by weight of Sc2W3O. 12 Micronized powder, 2-4 parts of nano-ZrO2, and 1-3 parts of B2O3 are ball-milled for 8-12 hours, with deionized water added and the glaze slurry specific gravity controlled at 1.45-1.65. During the process of heating to 1280-1320℃ at a controlled heating rate of 1-5℃ / min, the temperature is first raised from room temperature to 600℃ at a controlled heating rate of 1-2℃ / min; then raised to 1100℃ at a controlled heating rate of 2-4℃ / min; and finally raised to 1280-1320℃ at a controlled heating rate of 1-3℃ / min. The cooling rate during furnace cooling is less than 3℃ / min. Example 1

[0030] A high- and low-temperature resistant butterfly insulator includes a ceramic body and a glaze layer for coating the outer surface of the ceramic body. The ceramic body comprises 25 parts by weight of kaolin, 12 parts by weight of feldspar, 8 parts by weight of quartz, and 8 parts by weight of Sc2W3O. 12 The composition consists of core-shell powder, 3 parts high-entropy oxide, 2 parts B2O3, 0.5 parts P2O5, 0.3 parts Li2O, and 3 parts nano Al2O3.

[0031] Sc2W3O 12 Core-shell powder is composed of Sc2W3O 12 The core is composed of an Al₂O₃ shell. Sc₂W₃O 12 The core-shell powder was prepared by the sol-gel method, and the preparation method involved preparing Sc2W3O 12 Micronized powder was dispersed in an aluminum alkoxide solution, and after hydrolysis and condensation, an Al(OH)3 shell was formed. Then, pre-calcination was carried out at a controlled temperature of 590℃ to obtain an α-Al₂O₃ shell with a thickness of 0.25 μm and a Sc₂W₃O₃ shell with a D50 of 1 μm. 12 Sc2W3O composed of core layers 12 Core-shell powder. In the embodiments of this application, the aluminum alkoxide solution is an isopropanol solution of aluminum isopropoxide, and aluminum isopropoxide reacts with Sc2W3O. 12 The mass ratio of the micronized powders was 0.3:1. The pH of the hydrolysis and condensation solution was 4, the stirring speed was 200 r / min, and the hydrolysis time was 8 h.

[0032] It should be noted that the high-entropy oxide is (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O.

[0033] (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 The preparation method of O is as follows: Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2 are dissolved in deionized water in an equimolar ratio. Citric acid with a molar ratio of 1.2:1 to the metal ions is then added. The mixture is evaporated in a water bath at 78°C to form a gel. After pre-calcination at 380°C and high-temperature calcination at 780°C, high-entropy oxide powder with a particle size of 50-200 nm is obtained. The glaze layer consists of 70 parts by weight of a base glaze and 5 parts by weight of Sc2W3O. 12 Micronized powder, 2 parts nano ZrO2, and 1 part B2O3. The base glaze is a feldspar-quartz-lime glaze matrix, commercially available.

[0034] A method for preparing a high and low temperature resistant butterfly insulator, used to prepare the high and low temperature resistant butterfly insulator as described above, includes the following steps: Step 1, Ball Milling: Mix the appropriate weight parts of kaolin, feldspar, quartz, nano-Al2O3, and Sc2W3O 12 Core-shell powder, high-entropy oxide, B2O3, P2O5, and Li2O were mixed, and then ball-milled for 12 hours with the addition of deionized water and a dispersant to obtain a mixed slurry with a particle size D50 of 2.6 μm. Alumina grinding balls were used for ball milling, with a ball-to-powder mass ratio controlled at 2:1 and a rotation speed of 200 r / min. Sodium tripolyphosphate was used as the dispersant, and its addition amount was controlled at 0.2% of the total mass of the ceramic body.

[0035] Step 2, Iron Removal and Molding: The mixed slurry is sieved to remove iron, then pressed and vacuum-kneaded before molding to obtain the butterfly insulator porcelain blank. The molding process is isostatic pressing. The molding pressure is 150 MPa, and the holding time is 90 seconds. The slurry specific gravity for injection molding is 1.75, and the injection time is 15 minutes.

[0036] Step 3, Drying: Place the butterfly insulator porcelain blank in the shade at 40℃ for 48 hours, and then dry it at 100℃ until the moisture content is less than 0.5% to obtain the dried porcelain blank.

[0037] Step 4, Biscuit firing: Place the dried porcelain blank at a temperature of 850℃ for 2 hours, and then cool it to room temperature in the kiln to obtain the biscuit fired porcelain blank.

[0038] Step 5, Glazing and final firing: Glaze is applied to the surface of the bisque porcelain blank, and the glaze thickness is controlled to be 0.3 mm. Then, the heating rate is controlled to be 1-5℃ / min to raise the temperature to 1280℃, and the temperature is held for 4 hours and then cooled to room temperature with the furnace to obtain the finished high and low temperature resistant butterfly insulator.

[0039] The glazing process utilizes a glaze slurry applied via spraying, with the glaze thickness controlled to 0.3 mm. The glaze slurry consists of 70 parts by weight of a base glaze and 5 parts by weight of Sc2W3O. 12 Micronized powder, 2 parts nano-ZrO2, and 1 part B2O3 were ball-milled for 8 hours, with deionized water added and the glaze slurry specific gravity controlled at 1.45. During the process of heating to 1280℃ at a controlled heating rate of 1-5℃ / min, the temperature was first raised from room temperature to 600℃ at a controlled heating rate of 1℃ / min; then raised to 1100℃ at a controlled heating rate of 2℃ / min; and finally raised to 1280℃ at a controlled heating rate of 1℃ / min. The cooling rate during furnace cooling was less than 3℃ / min. Example 2

[0040] A high- and low-temperature resistant butterfly insulator includes a porcelain body and a glaze layer for covering the outer surface of the porcelain body. The porcelain body comprises 30 parts by weight of kaolin, 16 parts of feldspar, 10 parts of quartz, and 12 parts of Sc2W3O. 12 The composition consists of core-shell powder, 5 parts high-entropy oxide, 3 parts B2O3, 1 part P2O5, 1 part Li2O, and 4.5 parts nano Al2O3.

[0041] Sc2W3O 12 Core-shell powder is composed of Sc2W3O 12 The core is composed of an Al₂O₃ shell. Sc₂W₃O 12 The core-shell powder was prepared by the sol-gel method, and the preparation method involved preparing Sc2W3O 12 Micronized powder was dispersed in an aluminum alkoxide solution, and after hydrolysis and condensation, an Al(OH)3 shell was formed. Then, pre-calcination at a controlled temperature of 600℃ yielded an α-Al₂O₃ shell with a thickness of 0.3 μm and a Sc₂W₃O₃ shell with a D50 of 3.1 μm. 12 Sc2W3O composed of core layers 12 Core-shell powder. In the embodiments of this application, the aluminum alkoxide solution is an isopropanol solution of aluminum isopropoxide, and aluminum isopropoxide reacts with Sc2W3O. 12 The mass ratio of the micronized powders was 0.5:1. The pH of the hydrolysis and condensation solution was 5, the stirring speed was 350 r / min, and the hydrolysis time was 6 h.

[0042] It should be noted that the high-entropy oxide is (Mg 0.2 Co 0.2 Ni 0.2 Cu0.2 Zn 0.2 )O.

[0043] (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 The preparation method of O is as follows: Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2 are dissolved in deionized water in an equimolar ratio. Citric acid with a molar ratio of 1.5:1 to the metal ions is then added. The mixture is evaporated in a water bath at 80℃ to form a gel. After pre-calcination at 400℃ and high-temperature calcination at 800℃, high-entropy oxide powder with a particle size of 50-200 nm is obtained. The glaze layer consists of 75 parts by weight of a base glaze and 8 parts by weight of Sc2W3O. 12 Micronized powder, 3 parts nano ZrO2, and 2 parts B2O3. The base glaze is a feldspar-quartz-lime glaze matrix, commercially available.

[0044] A method for preparing a high and low temperature resistant butterfly insulator, used to prepare the high and low temperature resistant butterfly insulator as described above, includes the following steps: Step 1, Ball Milling: Mix the appropriate weight parts of kaolin, feldspar, quartz, nano-Al2O3, and Sc2W3O 12 Core-shell powder, high-entropy oxide, B2O3, P2O5, and Li2O were mixed, and then ball-milled for 18 hours with the addition of deionized water and a dispersant to obtain a mixed slurry with a particle size D50 of 3 μm. Alumina grinding balls were used for ball milling, with a ball-to-powder mass ratio controlled at 3:1 and a rotation speed of 300 r / min. Sodium tripolyphosphate was used as the dispersant, and its addition amount was controlled at 0.5% of the total mass of the ceramic body.

[0045] Step 2, Iron Removal and Molding: The mixed slurry is sieved to remove iron, then pressed and vacuum-kneaded before molding to obtain the butterfly insulator porcelain blank. The molding process is isostatic pressing. The molding pressure is 200 MPa, and the holding time is 60 seconds. The slurry specific gravity for injection molding is 1.85, and the injection time is 30 minutes.

[0046] Step 3, Drying: Place the butterfly insulator porcelain blank in the shade at 50℃ for 36 hours, and then dry it at 110℃ until the moisture content is less than 0.5% to obtain the dried porcelain blank.

[0047] Step 4, Biscuit firing: Place the dried porcelain blank at a temperature of 900℃ for 1.5 hours, and then cool it to room temperature in the kiln to obtain the biscuit fired porcelain blank.

[0048] Step 5, Glazing and final firing: Glaze is applied to the surface of the bisque porcelain blank, and the glaze layer thickness is controlled to be 0.5 mm. Then, the heating rate is controlled to be 1-5℃ / min to raise the temperature to 1300℃, and the temperature is held for 3 hours and then cooled to room temperature with the furnace to obtain the finished high and low temperature resistant butterfly insulator.

[0049] The glazing process utilizes a glaze slurry, applied via spray glazing, with the glaze thickness controlled to 0.5 mm. The glaze slurry consists of 75 parts by weight of a base glaze and 8 parts by weight of Sc2W3O. 12 Micronized powder, 3 parts nano-ZrO2, and 2 parts B2O3 were ball-milled for 10 hours, with deionized water added and the glaze slurry specific gravity controlled at 1.55. During the process of heating to 1300℃ at a controlled heating rate of 1-5℃ / min, the temperature was first raised from room temperature to 600℃ at a controlled rate of 1.5℃ / min; then raised to 1100℃ at a controlled rate of 3℃ / min; and finally raised to 1300℃ at a controlled rate of 2℃ / min. The cooling rate during furnace cooling was less than 3℃ / min. Example 3

[0050] A high- and low-temperature resistant butterfly insulator includes a porcelain body and a glaze layer for covering the outer surface of the porcelain body. The porcelain body comprises 35 parts by weight of kaolin, 20 parts by weight of feldspar, 14 parts by weight of quartz, and 15 parts by weight of Sc2W3O. 12 The composition consists of core-shell powder, 8 parts high-entropy oxide, 5 parts B2O3, 2 parts P2O5, 1.5 parts Li2O, and 6 parts nano Al2O3.

[0051] Sc2W3O 12 Core-shell powder is composed of Sc2W3O 12 The core is composed of an Al₂O₃ shell. Sc₂W₃O 12 The core-shell powder was prepared by the sol-gel method, and the preparation method involved preparing Sc2W3O 12 Micronized powder is dispersed in an aluminum alkoxide solution, and undergoes hydrolysis and condensation to form an Al(OH)3 shell. Pre-calcination at a controlled temperature of 610℃ yields an α-Al₂O₃ shell with a thickness of 0.5 μm and a Sc₂W₃O₃ shell with a D50 of 5 μm. 12 Sc2W3O composed of core layers 12 Core-shell powder. In the embodiments of this application, the aluminum alkoxide solution is an isopropanol solution of aluminum isopropoxide, and aluminum isopropoxide reacts with Sc2W3O. 12 The mass ratio of the micronized powders was 0.8:1. The pH of the hydrolysis and condensation solution was 6, the stirring speed was 500 r / min, and the hydrolysis time was 4 h.

[0052] It should be noted that the high-entropy oxide is (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2Zn 0.2 )O.

[0053] (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 The preparation method of O is as follows: Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2 are dissolved in deionized water in an equimolar ratio. Citric acid with a molar ratio of 1.8:1 to the metal ions is then added. The mixture is evaporated in a water bath at 82℃ to form a gel. After pre-calcination at 420℃ and high-temperature calcination at 850℃, high-entropy oxide powder with a particle size of 50-200 nm is obtained. The glaze layer consists of 80 parts by weight of a base glaze and 10 parts by weight of Sc2W3O. 12 Micronized powder, 4 parts nano ZrO2, and 3 parts B2O3. The base glaze is a feldspar-quartz-lime glaze matrix, commercially available.

[0054] A method for preparing a high and low temperature resistant butterfly insulator, used to prepare the high and low temperature resistant butterfly insulator as described above, includes the following steps: Step 1, Ball Milling: Mix the appropriate weight parts of kaolin, feldspar, quartz, nano-Al2O3, and Sc2W3O 12 Core-shell powder, high-entropy oxide, B2O3, P2O5, and Li2O were mixed, and after adding deionized water and a dispersant, the mixture was ball-milled for 24 hours to obtain a slurry with a particle size D50 of 4.6 μm. Alumina grinding balls were used for ball milling, with a ball-to-powder mass ratio controlled at 4:1 and a rotation speed of 350 r / min. Sodium tripolyphosphate was used as the dispersant, and its addition amount was controlled at 0.8% of the total mass of the ceramic body.

[0055] Step 2, Iron Removal and Molding: The mixed slurry is sieved to remove iron, then pressed and vacuum-kneaded before molding to obtain the butterfly insulator porcelain blank. The molding process is isostatic pressing. The molding pressure is 250 MPa, and the holding time is 90 seconds. The slurry specific gravity for injection molding is 1.90, and the injection time is 40 minutes.

[0056] Step 3, Drying: Place the butterfly insulator porcelain blank in the shade at 60℃ for 24 hours, and then dry it at 120℃ until the moisture content is less than 0.5% to obtain the dried porcelain blank.

[0057] Step 4, Biscuit firing: Place the dried porcelain blank at a temperature of 950℃ for 1 hour, and then cool it to room temperature in the kiln to obtain the biscuit fired porcelain blank.

[0058] Step 5, Glazing and final firing: Glaze is applied to the surface of the bisque porcelain blank, and the glaze thickness is controlled to be 0.6 mm. Then, the heating rate is controlled to be 1-5℃ / min to raise the temperature to 1320℃, and the temperature is held for 2 hours and then cooled to room temperature with the furnace to obtain the finished high and low temperature resistant butterfly insulator.

[0059] The glazing process utilizes a glaze slurry, applied via spray glazing, with the glaze thickness controlled to 0.6 mm. The glaze slurry consists of 80 parts by weight of base glaze and 10 parts by weight of Sc2W3O. 12 Micronized powder, 4 parts nano-ZrO2, and 3 parts B2O3 were ball-milled for 12 hours, with deionized water added and the glaze slurry specific gravity controlled at 1.65. During the process of heating to 1320℃ at a controlled rate of 1-5℃ / min, the temperature was first raised from room temperature to 600℃ at a controlled rate of 2℃ / min; then raised to 1100℃ at a controlled rate of 4℃ / min; and finally raised to 1320℃ at a controlled rate of 3℃ / min. The cooling rate during furnace cooling was less than 3℃ / min.

[0060] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that Comparative Example 1 uses Sc2W3O 12 Micronized powder as a substitute for Sc2W3O 12 Core-shell powder.

[0061] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that no high-entropy oxide was added in Comparative Example 2.

[0062] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that Sc2W3O was not added in Comparative Example 3. 12 Core-shell powder.

[0063] Performance testing: 1. Bending strength: The bending strength was obtained by testing according to GB / T 6569 "Test Method for Bending Strength of Fine Ceramics"; 2. Fracture toughness: The fracture toughness was obtained by testing in accordance with GB / T 23806 "Test Method for Fracture Toughness of Fine Ceramics"; 3. Thermal shock resistance: The thermal shock resistance test was conducted according to GB / T 16536 "Test Method for Thermal Shock Resistance of Engineering Ceramics" to obtain the number of thermal shocks at ΔT=400℃; 4. Electrical performance of insulators: In accordance with GB / T 1001.1 "Insulators for AC overhead lines with standard voltage higher than 1kV - Test methods", power frequency withstand voltage and temperature cycling (-40℃ to +80℃) tests were conducted to obtain the power frequency withstand voltage and breakdown voltage retention rate after temperature cycling. The performance test results are shown in Table 1 below.

[0064] Table 1 Performance Test Results Example 1 118 3.8 12 78 92 Example 2 135 4.5 15 85 95 Example 3 122 4.0 13 80 93 Comparative Example 1 112 3.2 6 75 82 Comparative Example 2 108 3.5 10 72 88 Comparative Example 3 95 2.8 3 68 70 As can be seen from Table 1 above, Sc2W3O in Example 2 12 Core-shell powder due to Sc2W3O 12 The synergistic effect of the core layer and Al2O3 shell results in excellent interfacial bonding with the ceramic body, and synergistically enhances the densification effect with high-entropy oxides, achieving optimal mechanical properties. Furthermore, Sc2W3O... 12 Core-shell powder significantly improves crack propagation resistance under the high lattice distortion effect of high-entropy oxides, thereby enhancing toughness. Comparative Example 1, lacking the interfacial buffering effect of the Al2O3 shell, results in Sc2W3O… 12 The interfacial bonding between the micropowder and the ceramic body decreased, resulting in reduced strength, reduced toughness, and a significantly shortened thermal shock life. Comparative Example 2, due to the lack of high-entropy oxides, suffered from insufficient density, leading to microcracks and a significant reduction in thermal shock performance. Comparative Example 3, due to the overall absence of Sc2W3O... 12 The performance of the micronized powder is significantly lower than that of the control group 1.

[0065] In summary, this application provides a high- and low-temperature resistant butterfly insulator and its preparation method. The high- and low-temperature resistant butterfly insulator prepared by this method utilizes Sc2W3O as a negative thermal expansion material. 12 The core powder and the positively expanding components in the ceramic body form a thermal expansion compensation effect, effectively reducing the coefficient of thermal expansion of the ceramic body and significantly improving the thermal shock resistance of the insulator under severe temperature alternation. Simultaneously, the Al2O3 shell exhibits good compatibility with the various components of the ceramic body, effectively avoiding the problems associated with Sc2W3O. 12 The thermal stress concentration phenomenon between the core layer and the ceramic body enhances the stability of temperature cycling. Simultaneously, the high-entropy effect and lattice distortion effect of high-entropy oxides effectively promote the densification of the ceramic body during sintering; and the dispersion strengthening of nano-Al2O3 and Sc2W3O... 12 The core-shell structure of the powder synergistically enhances the grain boundary bonding strength, thereby significantly improving the flexural strength and mechanical reliability of the ceramic body. To further improve the crack resistance and long-term service reliability of this high- and low-temperature resistant butterfly insulator, Sc2W3O is added to the glaze layer on the outer side of the ceramic body. 12 Micronized powder and B2O3 effectively regulate the thermal expansion coefficient of the glaze, avoiding problems such as cracking and peeling of the glaze caused by thermal expansion mismatch. In addition, the phase transformation toughening effect of nano ZrO2 improves the crack resistance of the glaze, so as to achieve long-term service reliability under extreme temperature conditions.

[0066] The terms “first,” “second,” “third,” “fourth,” etc., used in this application (if applicable) are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments described herein can be implemented in orders other than those described herein. Furthermore, the terms “comprising” and “having,” and any variations thereof, are intended to cover non-exclusive inclusion; for example, a process, method, or apparatus that includes a series of steps or units is not necessarily limited to those explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, or apparatus.

[0067] It should be noted that the descriptions using terms such as "first" and "second" in this application are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of those features. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. If the combination of technical solutions is contradictory or impossible to implement, such a combination of technical solutions should be considered non-existent and not within the scope of protection claimed in this application.

[0068] This document uses specific examples to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the methods and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A high and low temperature resistant butterfly insulator, comprising a ceramic body, characterized in that: The porcelain body comprises 25-35 parts by weight of kaolin, 12-20 parts by weight of feldspar, 8-14 parts by weight of quartz, and 8-15 parts by weight of Sc2W3O. 12 The composition consists of core-shell powder, 3-8 parts of high-entropy oxide, 2-5 parts of B2O3, 0.5-2 parts of P2O5, 0.3-1.5 parts of Li2O, and 3-6 parts of nano-Al2O3. in: The Sc2W3O 12 Core-shell powder is composed of Sc2W3O 12 The core is composed of an Al2O3 shell. The high-entropy oxide is (Mg) 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O.

2. The high and low temperature resistant disc insulator according to claim 1, characterized in that: The Sc2W3O 12 The core-shell powder was prepared by the sol-gel method, and the preparation method involved preparing Sc2W3O 12 Micronized powder is dispersed in an aluminum alkoxide solution, and undergoes hydrolysis and condensation to form an Al(OH)3 shell. Pre-calcination at a controlled temperature of 590-610℃ yields an α-Al₂O₃ shell with a thickness of 0.2-0.5 μm and a Sc₂W₃O₃ shell with a D50 of 1-5 μm. 12 Sc2W3O composed of core layers 12 Core-shell powder.

3. A high and low temperature resistant disc insulator according to claim 2, characterized in that: The aluminum alkoxide solution is an isopropanol solution of aluminum isopropoxide, and aluminum isopropoxide reacts with Sc2W3O. 12 The mass ratio of the micro powder is (0.3-0.8):1; the pH of the hydrolysis and condensation solution is 4-6, the stirring speed is 200-500 r / min, and the hydrolysis time is 4-8h.

4. A high and low temperature resistant disc insulator according to claim 1, characterized in that: The (Mg) 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 The preparation method of O is as follows: Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2 are dissolved in deionized water in an equimolar ratio, and then citric acid is added and evaporated in a water bath to form a gel. After pre-calcination and high-temperature calcination, high-entropy oxide powder with a particle size of 50-200 nm is obtained. The molar ratio of citric acid to metal ions is (1.2-1.8):1; the water bath evaporation temperature is 78-82℃; the pre-calcination temperature is 380-420℃; and the high-temperature calcination temperature is 780-850℃.

5. A high and low temperature resistant disc insulator according to claim 1, characterized in that: It also includes a glaze layer for coating the outer surface of the porcelain body; the glaze layer comprises 70-80 parts by weight of a base glaze and 5-10 parts by weight of Sc2W3O 12 Micronized powder, 2-4 parts of nano ZrO2 and 1-3 parts of B2O3; the base glaze is a feldspar-quartz-lime glaze matrix.

6. A method for preparing a high and low temperature resistant butterfly insulator, used to prepare a high and low temperature resistant butterfly insulator as described in any one of claims 1-4, characterized in that, Includes the following steps: Step 1, Ball Milling: Mix the appropriate weight parts of kaolin, feldspar, quartz, nano-Al2O3, and Sc2W3O 12 Shell-core powder, high-entropy oxide, B2O3, P2O5 and Li2O are mixed, and after adding deionized water and dispersant, the mixture is ball-milled for 12-24 hours to obtain a mixed slurry with a particle size D50 of 2-5μm. Step 2, Iron Removal and Molding: The mixed slurry is sieved to remove iron, and after pressing and vacuum kneading, it is shaped to obtain the butterfly insulator porcelain blank; Step 3, Drying: Place the butterfly insulator porcelain blank in the shade at a temperature of 40-60℃ for 24-48 hours, and then dry it at a temperature of 100-120℃ until the moisture content is less than 0.5% to obtain the dried porcelain blank; Step 4, Biscuit firing: Place the dried porcelain blank at a temperature of 850-950℃ for 1-2 hours, and then cool it to room temperature in the kiln to obtain the biscuit fired porcelain blank. Step 5, Glazing and final firing: Apply glaze to the surface of the bisque porcelain blank, control the glaze thickness to be 0.3-0.6mm, then control the heating rate to 1-5℃ / min to raise the temperature to 1280-1320℃, hold for 2-4 hours and cool with the furnace to room temperature to obtain the finished high and low temperature resistant butterfly insulator.

7. The method for preparing a high and low temperature resistant disc insulator according to claim 6, characterized in that: In step 1, the alumina grinding balls are used for ball milling, and the ball-to-material mass ratio is controlled at (2-4):1, with a rotation speed of 200-350 r / min; the dispersant is sodium tripolyphosphate or ammonium polyacrylate, and the amount added is controlled at 0.2-0.8% of the total mass of the ceramic body.

8. The method for preparing a high and low temperature resistant disc insulator according to claim 6, characterized in that: In step 2, the molding process is either isostatic pressing or grouting. The molding pressure for isostatic pressing is 150-250 MPa, and the holding time is 30-90 s. The grout for grouting has a specific gravity of 1.75-1.90, and the grouting time is 15-40 min.

9. The method for preparing a high and low temperature resistant disc insulator according to claim 6, characterized in that: In step 5, the glazing is performed using a glaze slurry, either by dipping or spraying, with the dipping time controlled to be 3-8 seconds or the spraying thickness to be 0.3-0.6 mm. The glaze slurry consists of 70-80 parts by weight of a base glaze and 5-10 parts by weight of Sc2W3O. 12 Micronized powder, 2-4 parts of nano ZrO2 and 1-3 parts of B2O3 are ball-milled for 8-12 hours, and deionized water is added and the specific gravity of the glaze slurry is controlled to be 1.45-1.

65.

10. A method for preparing a high and low temperature resistant disc insulator according to claim 6, characterized in that: In step 5, the temperature is first raised from room temperature to 600℃ at a rate of 1-2℃ / min; then raised to 1100℃ at a rate of 2-4℃ / min; and finally raised to 1280-1320℃ at a rate of 1-3℃ / min. The cooling rate during furnace cooling is less than 3℃ / min.